2015
DOI: 10.1002/2014jb011496
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanisms of creep in clay‐rich gouge from the Central Deforming Zone of the San Andreas Fault

Abstract: We report the strength and constitutive behavior of gouge sampled from the Central Deforming Zone (CDZ) of the San Andreas Fault. Layers of flaked CDZ gouge were sheared in the triaxial saw cut configuration using the stress relaxation technique to measure the gouge strength over 4 orders of magnitude in shear strain rate and at rates as low as 5 × 10 −10 s −1 and within an order of magnitude of in situ rates. Deformation conditions correspond to the in situ effective normal stress (100 MPa) and temperature (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 74 publications
6
30
0
Order By: Relevance
“…In clay‐rich fault rock, records of frictional heating during seismic slip are challenging to preserve unless the rock melted, in part because dehydration is a reversible process and decomposition products can be difficult to identify as such. Recent detailed structural analyses of carbonate fault gouges and rocks have shown that dynamic weakening processes can be recorded in the fabric of the fault rock (Bullock et al, ; Rempe et al, ; Smith et al, ), and herein we present additional evidence that the structures that form in clay‐rich fault rocks at seismic slip rates and low effective normal stress are distinct from those that have been shown to develop at subseismic deformation rates (e.g., French et al, ; Logan et al, ).…”
Section: Lithologic Controls Of Slip Localizationsupporting
confidence: 65%
See 3 more Smart Citations
“…In clay‐rich fault rock, records of frictional heating during seismic slip are challenging to preserve unless the rock melted, in part because dehydration is a reversible process and decomposition products can be difficult to identify as such. Recent detailed structural analyses of carbonate fault gouges and rocks have shown that dynamic weakening processes can be recorded in the fabric of the fault rock (Bullock et al, ; Rempe et al, ; Smith et al, ), and herein we present additional evidence that the structures that form in clay‐rich fault rocks at seismic slip rates and low effective normal stress are distinct from those that have been shown to develop at subseismic deformation rates (e.g., French et al, ; Logan et al, ).…”
Section: Lithologic Controls Of Slip Localizationsupporting
confidence: 65%
“…In fault gouge that has rate‐strengthening constitutive properties, like the CDZ gouge (Carpenter et al, ; Coble et al, ; French et al, ; Lockner et al, ), coseismic shear heating and resultant thermal pressurization can cause the apparent slip weakening and rate weakening observed in the CDZ gouge (French et al, ; Rice, ). Such thermally driven coseismic processes can also cause the localization of inherently slip‐ or rate‐strengthening fault rocks to a localized slip zone that has finite thickness (Rice, ; Rice et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictions of mechanical and transport properties over long timescales are essential for the evaluation of subsurface integrity. For this, it is generally agreed that a multiscale experimental approach that combines measurement of bulk mechanical and transport properties with microstructural study to identify deformation mechanisms is required to develop microphysics-based constitutive equations, which can be extrapolated to timescales not available in the laboratory, after comparison with naturally deformed specimens (Morgenstern and Tchalenko, 1967;Tchalenko, 1968;Lupini et al, 1981;Rutter et al, 1986;Logan et al, 1979Logan et al, , 1987Logan et al, , 1992Marone and Scholz, 1989;Evans and Wong, 1992;Katz and Reches, 2004;Niemeijer and Spiers, 2006;Colletini et al, 2009;Haines et al, 2009Haines et al, , 2013French et al, 2015;Crider, 2015;Ishi, 2016).…”
Section: Introductionmentioning
confidence: 99%